Perbedaan Efektivitas Latihan Handgrip Isometrik dan Relaksasi Autogenik terhadap Perubahan Tekanan Darah Penderita Hipertensi - Heri Bahtiar; Maelina Ariyanti; Dewi Nur Sukma Purqoti; Bq Nurainun Apriani Idris (LPPM STIKES Mataram, 2023)
Introduction: non-communicable diseases group that are very common and easy to detect in society is hypertension. Hypertension is a non-communicable disease which is often called the silent killer disease and serious problem that needs to be watched out for. Hypertension is a condition where there is an increase on blood pressure above normal which can result in increased morbidity and mortality. Purpuse: the aimed of this research was to identify the effect of soaking feet in warm water with red ginger mixture on blood pressure in hypertensive patients. Method: the research design used was Pre-Experiment with the One Group Pretest – Posttest approach. The population and sample used in this research were 16 people with 6 patients with mild hypertension and 10 people with moderate hypertension. Data analysis using the T-Test test. Result: the results of this research show that P value of 0.00 <0.05, meaning that there is an effect of soaking feet in warm water with red ginger and salt mixture toward blood pressure in hypertensive patients at Lingsar Public Health Center. Suggestion: This research shows that soaking feet in warm water with red ginger and salt mixture can reduce blood pressure on hypertension so that it can be done routinely and without having to use drugs.